Decolonization in Britain and France: The Domestic Consequences of International Relations - MILES KAHLER (Princeton University Press, 2014)
THE FIRST glimmerings of this study came during the Vietnam War, when, as a student, I attempted to comprehend the choice of an imperial role and the opposition that it inspired, at home and abroad. By the time that I began the first version of this study, my interest had been transformed into a concern with societies that lose their empires and are forced to adjust their self-images and their domestic politics. In the course of that investigation, I become increasingly dissatisfied with the existing, rigid division between the fields of international relations and domestic political development. The substantive problem of domestic adaptation to international change and the theoretical dissatisfaction lie at the base of this book.